2016
DOI: 10.1007/s00299-016-2064-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of omics approaches to understand oil/protein content during seed development in oilseed crops

Abstract: Oilseed crops, especially soybean (Glycine max) and canola/rapeseed (Brassica napus), produce seeds that are rich in both proteins and oils and that are major sources of energy and nutrition worldwide. Most of the nutritional content in the seed is accumulated in the embryo during the seed filling stages of seed development. Understanding the metabolic pathways that are active during seed filling and how they are regulated are essential prerequisites to crop improvement. In this review, we summarize various om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 145 publications
5
53
0
Order By: Relevance
“…Studies have shown that some miRNAs and their target genes are related to seed size [13,46], and most of the target genes belong to transcription factors, mainly ARF [19,47], CNR [48] and MYB [49]. Our data showed there were 23 miRNA-mRNA Because MYB89 transcription factor represses seed oil accumulation in Arabidopsis, and it was expressed predominantly in developing seeds during maturation [50].…”
Section: Identification Of Mirnas In Developing Seeds Of Tea Oil Camementioning
confidence: 57%
See 1 more Smart Citation
“…Studies have shown that some miRNAs and their target genes are related to seed size [13,46], and most of the target genes belong to transcription factors, mainly ARF [19,47], CNR [48] and MYB [49]. Our data showed there were 23 miRNA-mRNA Because MYB89 transcription factor represses seed oil accumulation in Arabidopsis, and it was expressed predominantly in developing seeds during maturation [50].…”
Section: Identification Of Mirnas In Developing Seeds Of Tea Oil Camementioning
confidence: 57%
“…The miR156 participates in the early morphogenesis of Arabidopsis embryos by regulating target SPL10 and SPL11 [27], and it may also mediate the targeted regulation of SBP expression levels to affect flowering time in plants [47]. miR159…”
Section: Mirnas-target Genes Involved In Growth and Development In Tementioning
confidence: 99%
“…One example of translating fundamental research into benefit for farmers is the Water Efficient Maize for Africa (WEMA) project which aims to develop drought-tolerant and insect-protected maize using conventional breeding, marker-assisted selection, and biotechnology approaches [25]. Omics has also been used to investigate the regulation of oil biosynthesis with the objective of increasing yields of oil crops [14,28].…”
Section: Investigation Of Oil Yield Using Omicsmentioning
confidence: 99%
“…Moreover, this approach gives insight in a time dimension -i.e. it allows seed germination and development to be addressed (Wang et al, 2016;Gupta, Bhaskar, Sriram, and Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%